Clinical researchMorphogenetic aspects of the septomarginal trabecula in the human heart - Kosiński, Adam; Kozłowski, Dariusz; Nowiński, Janusz; Lewicka, Ewa; Dąbrowska-Kugacka, Alicja; Raczak, Grzegorz; Grzybiak, Marek (Archives of Medical Science, 2010)
Introduction: The septomarginal trabecula is a constant element of the anatomy of the human heart, which connects the interventricular septum and the anterior wall of the right ventricle. Considering the diversity of opinions about the structure and numerous studies suggesting its important role in haemodynamics and conduction of electrical impulses in the heart, we decided to study this element in detail. Material and methods : The research was conducted on 220 human hearts. Attention was mainly paid to the structure and topography of the trabecula. Its relation to the anterior papillary muscle was also a part of the study. Results : The presence of this morphologically diverse element was confirmed in each of the studied hearts. In most cases the trabecula originated from the upper part of the interventricular septum, separating at an angle increasing proportionally to the number of branches of the crista supraventricularis as well as the number of secondary trabeculae. The criteria established for the study, which included the course of the trabecula in the lumen of the right ventricle and its relation to the anterior papillary muscle, let us distinguish 4 types of septomarginal trabecula (I, II, III, IV). The most common was type III, the undivided trabecula, tightly connecting with the anterior papillary muscle. Conclusions : Based on the results of the following study we propose a hypothesis on the genesis of respective parts of the septomarginal trabecula and a plausible sequence of changes they undergo during human ontogenesis and phylogenesis of the primates.